Antisocial Personality Disorder - Cunningham, Muriel (MD Conference Express, 2007)
Although the DSM-IV clearly outlines the seven criteria used to diagnose antisocial personality disorder, it is often a categorical diagnosis. In order to truly understand and effectively treat an individual presenting with antisocial personality disorder, clinicians must use the DSM-IV criteria in conjunction with a multi-dimensional view of the disorder.